First assessment of hydrogen/brine/Saudi basalt wettability: implications for hydrogen geological storage - Alanazi, Amer; Al-Yaseri, Ahmed; Mowafi, Mahmoud; Leila, Mahmoud; Hoteit, Hussein (Frontiers in Earth Science, 2023)
Underground hydrogen (H2) storage is a prominent technique to enable a large-scale H2based economy as part of the global energy mix for net-zero carbon emission. Recently, basalts have gained interest as potential caprocks for subsurface H2 storage due to their low permeability, vast extension, and potential volumetric capacity induced by structural entrapment of the buoyant H2. Wettability represents a fundamental parameter which controls the capillary-entrapment of stored gases in porous media. The present study evaluates the wettability of basalt/H2/brine system of two basalt samples from Harrat Uwayrid, a Cenozoic volcanic field, in Saudi Arabia. The H2/basalt contact angle was measured using a relevant reservoir brine (10% NaCl) under storage conditions of 323K temperature and pressure ranges from 3 to 28 MPa using the modified sessile drop method. The surface roughness of the basaltic rocks was determined to ensure accurate results. The investigated Saudi basalt samples are water-wet, thereby they did not achieve a 100% hydrogen wetting phase even at 28 MPa pressure. The measured contact angles slightly decrease as pressure increases, thereby pressure did not significantly influences the height of the H2 column.We interpret this trend to the slight increase in H2 density with increasing pressure as well as to the olivine-rich mineralogical composition of the Saudi basalt. Thus, from the wettability aspects, Saudi basalt has the potential to store a large volume of H2 (> 1400 m height) and maintain its excellent storage capacity even in deep, high-pressure regimes. This study demonstrates that the basalt rock texture (pore throat radii) and mineralogy control their capacity for subsurface H2 storage.